2000
DOI: 10.1542/peds.105.3.e35
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus: Reemerging Central Nervous System Pathogen

Abstract: ABSTRACT. Lymphocytic choriomeningitis virus (LCMV), a human zoonosis caused by a rodent-borne arenavirus, has been associated with both postnatal and intrauterine human disease. Infection in man is acquired after inhalation, ingestion, or direct contact with virus found in the urine, feces, and saliva of infected mice, hamsters, and guinea pigs. Congenital LCMV infection is a significant, often unrecognized cause of chorioretinitis, hydrocephalus, microcephaly or macrocephaly, and mental retardation. Acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 15 publications
0
50
0
Order By: Relevance
“…LCMV usually cause aseptic meningitis, but encephalitis may be diagnosed in about 5% to 34% of serologically confirmed LCMV cases 22 . Other neurological complications reported are ascending paralysis, bulbar syndromes, Parkinsonism features, and sensorineural hearing loss.…”
Section: Lymphocytic Choriomeningitis Virus (Lcmv)mentioning
confidence: 99%
“…LCMV usually cause aseptic meningitis, but encephalitis may be diagnosed in about 5% to 34% of serologically confirmed LCMV cases 22 . Other neurological complications reported are ascending paralysis, bulbar syndromes, Parkinsonism features, and sensorineural hearing loss.…”
Section: Lymphocytic Choriomeningitis Virus (Lcmv)mentioning
confidence: 99%
“…LCMV infection in a pregnant woman can spread to the fetus, resulting in abortion early in pregnancy (Deibel et al, 1975) or malformations, including hydrocephalus, intracranial calcifications, and chorioretinitis if the infection occurs later in pregnancy (Ackermann et al, 1974;Sheinbergas, 1975;Barton et al, 1993Barton et al, , 1996Wright et al, 1997;Marrie and Saron, 1998;Barton and Hyndman, 2000;Jamieson et al, 2006;Bonthius et al, 2007b). A study by Bonthius and colleagues (2007b) reports on 20 children with serologically confirmed congenital LCMV infection who were followed for up to 11 years.…”
Section: Lcmv Infection In Pregnancymentioning
confidence: 99%
“…Congenital LCMV infection acts as an abortifacient and a fetal teratogen commonly manifested as chorioretinitis, hydrocephalus and microcephaly or macrocephaly (5-9). Adult infection with LCMV can lead to the development of fever, malaise, headaches, seizure and in some cases fatal meningitis (3,(10)(11)(12)(13). Through the study of murine models of infection, a mechanistic understanding of LCMV induced immunopathology can be gained and applied to human disease.…”
Section: General Background On Lcmvmentioning
confidence: 99%